Coming to America: does immigrant's home country economic status impact the probability of self-employment in the U.S.? - Ruth Uwaifo Oyelere; Willie Belton (Institute for the Study of Labor (IZA), 2009)
This paper examines the impact of home country economic status on immigrant self-employment probability in the U.S. We estimate a probability model and find that, consistent across race, immigrants from developed countries are more likely to be self-employed in the U.S than are immigrants from developing countries. This result is unexpected given previous research which suggests that immigrants from countries with high levels of self-employment tend to be more involved in self-employment in the U.S. Developing countries on average have higher self-employment rates than do developed countries but our research shows that immigrants from developing countries have similar or lower self-employment probabilities relative to native born White Americans, whereas immigrant from developed countries have significantly higher self-employment probabilities relative to native born White Americans. We provide two potential explanations for this result. First, immigrants from developed countries may indeed have more and better access to start-up capital from their country of origin. Second, institutional arrangements in the developed world may be similar across countries allowing immigrants from developed countries to have an informational advantage over immigrants from developing countries.
urn:nbn:de:101:1-2009060893
Keywords: J21; E24; J61; J40; 330; Self-employment; immigrant; home country; entrepreneurship; Migranten; Einwanderung; Selbstständige; Unternehmer; Sozialer Status; USA